'There is something special about the church' – a study of wedding couples in the Evangelical-Lutheran Church in Denmark. Issue 5 (20th October 2019) - Johansen, Kirstine Helboe
ABSTRACT: This article presents analytical findings of an explorative, qualitative study of the understanding of the wedding ritual among couples in the Evangelical-Lutheran Church in Denmark, conducted in 2012. In a combination of ritual theories and theories from the sociology of religion, the analysis explores what kind of ritual understandings wedding couples express when talking about their wedding. Depending on the degree and way in which wedding couples express wishes to personalise ritual, two ideal types, traditionalists and selective, are constructed. By the end, I discuss similarities between personalisation of established rituals and self-constructed ritualisation. Furthermore, I point to a need for understanding the meaning of established rituals as emerging in the meeting point between ritual order and participants.